Radical Fragility: Building Inclusive Educational Experiences Through Art - Paris Romia, Gemma; Blanch-Gelabert, Silvia (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2025)
The incorporation of the arts into education can be understood as an act of radical fragility, as it opens spaces of sensitivity, attentiveness, and speculative thinking in environments often dominated by standardization and efficiency. Viewing artistic research as a legitimate form of knowledge means recognizing artistic practice as a way of understanding the world expressed through multiple languages and deeply rooted in the life experiences of those who create. It is not enough to offer children occasional exposure to artistic techniques; it is essential to create the conditions for them to engage in artistic inquiry. This fosters imagination, intuition, and critical thinking at the heart of their development. Such an approach can only be sustained if educators are themselves involved in artistic practice or if strong, ongoing collaborations are established with active artists who are not merely external guests but embedded in the educational process. Although some educational initiatives successfully integrate the arts, these remain the exception. In most schools, the arts still occupy a marginal and fragmented role, limiting students’ opportunities to connect their thinking with open-ended forms of creation and sensitivity.This article explores two meaningful examples of deep artistic integration in education. The first is the legacy of Ruth Asawa (1926–2013), an artist and educator who lived creativity as a continuous process, intertwining her sculptural work with motherhood and teaching. For Asawa, art and education were not separate spheres, but interdependent aspects of life. Inspired by this example among others, the European project Interstice. Encounters between artists, children & educators brings together teachers and artists across Europe. It promotes the integration of visual and performing arts into learning from early childhood to university. Here, we share insights from this project as evidence of how the arts can become a central force for educational innovation, collective sensitivity, and social transformation.
Keywords: artists; art thinking; cocreation; education; nursery teacher